Application of magnetic method for mapping buried structures around archaeological site of Masjid Tuha Indrapuri - CUT INTAN KEUMALA; TOMI AFRIZAL; MUHAMMAD SYUKRI SURBAKTI; NAZLI ISMAIL (Jurnal Natural, 2020)
Magnetic gradiometer survey has been conducted on the yard of the archaeological site of Masjid Tuha Indrapuri, Aceh Besar Regency, Aceh Province. The site is one of the oldest mosques erected during the Aceh Sultanate period. Magnetic method was applied for mapping archaeological structures buried beneath the surface. Total magnetic field data were measured using Proton Precession Magnetometer with grid spacing of 2 meters between stations covering the entire area of the site. Diurnal and international geomagnetic reference field data were corrected to the measured data in order to calculate total magnetic field anomalies that were influenced by the buried magnetic objects. The total magnetic field anomalies distribution shows two elongated structures with U-shaped patterns surrounding the mosque. The patterns are also revealed in reduction to the pole and derivative vertical filters of the total field anomaly data. The anomaly patterns are considered a response from the rest of the buried fences that were built around the mosque in the past.